Pulmonary damage in a patient with hairy cell leukemia - infectious involvement or hematological disease activity? Case report - Ecsiova, Dominika; Kamaradova, Katerina; Nova, Marketa; Hoffmann, Petr; Rozsivalova, Petra; Simkovic, Martin; Zak, Pavel (Biomedical papers, 2023)
Background. Hairy cell leukemia (HCL) is a rare indolent lymphoproliferative disease with an accumulation of mature B lymphocytes with fine reticular chromatin and cytoplasm with typical hairy-like cytoplasmic projections. Rarely, hairy cell leukemia manifests as a lung infiltration. The differential diagnosis between infection and malignant involvement with hairy cell leukemia is often challenging in such situations.Methods and Results. We present a 53-year-old female with an uncommon pulmonary involvement with hairy cell leukemia. In addition, we discuss the complicated differential diagnosis of pulmonary disease in patients with hairy cell leukemia and the treatment approach to these patients.Conclusion. This case report describes the successful therapy management of a patient with pulmonary involvement by hairy cell leukemia. Therapy with interferon-alfa and cladribine resulted in long-term remission of the underlying disease.
Keywords: hairy cell leukemia; pulmonary infiltration; interferon-alfa; cladribine